Peran Guru Pendidikan Agama Islam Dalam Mencegah Perilaku Bullying di SMP Terpadu Nurul Fattah Dadapan - Zamroni, Ahmad; Junaidi, Mahbub (Fakultas Agama Islam, 2025)
In the adolescent stage, individuals experience rapid learning and talent development. However, this phase is also often accompanied by poor decision-making due to external influences such as peer pressure and technology. Adolescents who lack parental supervision tend to seek pleasure outside the home and often fall into negative behaviors, including bullying. Bullying is an aggressive act that is carried out continuously with the aim of hurting, oppressing and torturing the victim for the personal satisfaction of the perpetrator without compassion. This phenomenon not only occurs in primary and secondary schools but also in tertiary institutions, making it a serious problem that needs to be addressed. In this context, Islamic Religious Education (PAI) has an important role not only as an academic subject but also as a means to shape students' character and morals. PAI can provide moral and ethical values that are important in preventing and reducing cases of bullying in the educational environment. Therefore, the role of Islamic Religious Education teachers is very significant in creating a safe and supportive school environment, where students can develop good character and avoid bullying behavior.